Childhood obesity [ prevalence, pathophysiology and management - Ahima, Rexford S. (CRC Press, 2014)
The prevalence of childhood overweight and obesity has increased worldwide in recent decades. Obesity in childhood is associated with a wide range of serious health complications and an increased risk of premature illness and death later in life. This book presents childhood obesity trends across multiple demographics. It discusses the contributing genetic and environmental factors of childhood obesity and shows the adverse health consequences of childhood obesity, both as they relate to childhood and as they last into adulthood. It also presents multiple methods for obesity treatment, including community and family-based intervention, pharmacotherapy, and surgical procedures -- Book Jacket